RUTILE-QUARTZ GEOTHERMOBAROMETER - Ostapenko G.T.; Mitsyuk B.M.; Tarashchan A.N. (My University, 2007)
The system quartz with dissolved íiO2–rutile is of particular interest for geochemistry. Several authors described bluish quartz grains with rutile needles from the granulites, charnockites, and gneisses of shield regions. Rutile in quartz was considered as an exsolution product formed under decreasing temperature from the (Si, Ti)O2 solid solution.